2006
DOI: 10.1007/s10103-006-0404-z
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effect of a gastric ischemia–reperfusion model with laser Doppler blood perfusion imaging

Abstract: The objectives of this study are to establish a gastric ischemia-reperfusion model and test it using the laser Doppler blood perfusion imaging (LDPI) method and to evaluate the role of the LDPI technique in the measure of gastric blood circulation. The right gastric artery of the rat was clamped for 30 min and then reperfused. The LDPI was used to display the blood circulation of the whole gastric surface during this process. The blood flow perfusion image of the gastric surface was displayed clearly. After th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…LDPI can detect microcirculation status after a direct stress reaction and has been widely used in clinical diagnosis, evaluation, and research associated with microcirculation such as acupuncture [35] and skeletal muscle microcirculation [36]. We measured the number of perfusion units in this study: PU = CMBC (the concentration of measuring the volume inside the blood cells) × V (the average velocity of blood cells).…”
Section: Resultsmentioning
confidence: 99%
“…LDPI can detect microcirculation status after a direct stress reaction and has been widely used in clinical diagnosis, evaluation, and research associated with microcirculation such as acupuncture [35] and skeletal muscle microcirculation [36]. We measured the number of perfusion units in this study: PU = CMBC (the concentration of measuring the volume inside the blood cells) × V (the average velocity of blood cells).…”
Section: Resultsmentioning
confidence: 99%
“…Imaging methods to evaluate HMP by directly monitoring the overall HM remain lacking. Our laboratory applied laser Doppler blood flow imaging and LSPI technology for the first time to display perfusion over the entire surface of an animal stomach 28 . On this basis, this study established a liver LSPI method for the intuitive and dynamic observation of the HMP in livers with alcoholic injury.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that acupuncture treatment can improve hemorheology and vasoactive substances, such as thromboxane A 2 (TXA 2 ), prostaglandin I 2 (PGI 2 ), endothelin (ET), and atrial natriuretic factor (ANF) [ 5 ]. Zhang et al [ 6 ] reported that blood supply in the stomach of ischemia-reperfusion is improved and promoted by EA stimulation. Therefore, the increase of visceral blood perfusion (BP) is an important effect of acupuncture and a basis in the acupuncture treatment for visceral diseases [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%